Antidepressant activity of Channa striatus Bloch extracts in rodents and their possible mechanism - Abdul Shukkoor, Mohamed Saleem (2016)
Depression is a major mood disorder. Despite the availability of effective pharmacotherapy, around 30% of patients do not respond to current treatments. Several natural products exhibited antidepressant activity in previous studies. Channa striatus (Malay: Haruan) exhibited antinociceptive effect in mice through serotonergic system. Dysfunction of serotonergic system has been associated with depression and many antidepressant drugs act through it. Hence, this study evaluated the antidepressant activity of extracts of C. striatus in rodents and their mechanism of action. Aqueous and lipid extracts were prepared from the fillet of C. striatus and their individual components were quantified. Both extracts were tested in forced swimming test (FST), tail suspension test (TST) and open field test (OFT) in male ICR mice. The mechanism of action was evaluated by pretreatment with selected monoamine antagonists. The lipid extract was tested in postpartum depression (PPD) model in female Sprague-Dawley rats and chronic unpredictable mild stress model (CUMS) in male Sprague-Dawley rats through FST and OFT. The plasma levels of corticosterone, oxytocin, brain prefrontal cortex and hippocampal levels of monoamines, brain-derived neurotrophic factor (BDNF), interleukin-6 (IL-6) and nuclear factor-kappa B (NF-κB) were determined by ELISA in PPD and CUMS experiments. Additionally, body weight and sucrose preference were measured at every week during CUMS study. Analysis of variance followed by appropriate post hoc test was used as the statistical test with significance considered at p < 0.05. The aqueous extract produced significant (p < 0.001) antidepressant activity in FST and TST and its mechanism was found to be acting through the serotonergic system and noradrenergic system. In another experiment, aqueous and lipid extracts, prepared by a different method, produced significant (p < 0.05) antidepressant activity in FST and TST through serotonergic and noradrenergic systems. The lipid extract was found to contain oleic acid, palmitic acid as major fatty acids along with docosahexaenoic acid. The aqueous extract was found to contain aspartic acid and glutamic acid as major amino acids. The lipid extract produced significant (p < 0.001) antidepressant effect in PPD model, with the mechanism mediated through the decrease in corticosterone, increase in oxytocin and decrease in NF-κB in prefrontal cortex. The lipid extract produced significant (p < 0.001) antidepressant effect in FST in CUMS model, with the mechanism mediated through the decrease in corticosterone, increase in serotonin level in prefrontal cortex, increase in dopamine and noradrenaline levels in hippocampus and prefrontal cortex, increase in BDNF level in hippocampus and prefrontal cortex, and decrease in IL-6 and NF-κB levels in prefrontal cortex. The lipid extract also significantly (p < 0.05) reversed the effects of stress on body weight of animals and sucrose preference in CUMS model. In conclusion, the aqueous and lipid extracts of C. striatus produced significant antidepressant effect in animal models of depression with the common mechanism of action through monoaminergic systems. These findings may be useful to explore further the clinical utility and molecular mechanism of action of these extracts.